Analysis of repulsed dust from electrostatic curtain using different voltages - Abdullah, M M.; Al-Ansari, M; Ayad, R (Sulaimani Journal for Pure and Applied Sciences, 2015)
Naturally dust particles are statically charged, they settle down on different surfaces. Experiments were conducted to study the rolled off dust particles from the surface of an electrostatic curtain. The value of the applied dc voltages to the electrostatic curtain is considered along with the diameters of accumulated dust particles. For this purpose, dust was collected and classified into three categories depending on the values of the particle diameter (20, 40 and 56 µm). Fluorescence X-Ray results showed that the dust is composed of various elements such as lead, silver, nickel, copper and many others. The presence of those elements on the charged electrostatic curtain depends on their electrical conductivity and molecular weight.